FORMULATION AND EVALUATION OF EDIBLE FILM BETEL (PIPER BETLE L.) LEAVES EXTRACT AS MOUTH FRESHNER - NURDIANTI, LUSI; APRILLIA, ADE YENI; NURDALIS, SRI; INDRA (International Journal of Applied Pharmaceutics, 2022)
Objective: The purpose of this study is to create and assess edible film formulations from betel (Piper betle L.) leaf extract that may be used to treat Streptococcus mutans bacteria-caused halitosis. Methods: Using ethanol as a solvent, the extraction process was employed to produce a concentrated extract of betel leaf. To find the minimum dose that could suppress bacteria development, the antibacterial activity of the ethanol extract of betel leaf was studied on streptococcus bacteria. The dosage of the betel leaf ethanol extract formula and the creation of edible film formulations are then based on the results of the antibacterial activity and evaluation of edible films. Results: The ethanol extract of betel leaf and edible film formulations can both prevent the growth of S. mutans bacteria, according to the results of the antibacterial activity test. The evaluation's findings demonstrate that the three edible film formulations of betel leaf ethanol extract satisfy the Indonesian National Standard's requirements (SNI). When compared to the other formula. Formula 3 demonstrated the strongest antibacterial activity. Conclusion: According to the study's findings, it is possible to apply the ethanol extract of betel leaf in the form of an edible film. S. mutans bacteria can have their growth inhibited by betel leaf ethanol extract. The betel leaf ethanol extract edible film formula has satisfied the criteria, and formula 3 was the best edible film formula.